KARAKTERISTIK GALAKTOMANAN DARI BERBAGAI SUMBER DAN PEMANFAATANNYA SEBAGAI BAHAN TAMBAHAN PADA PRODUK PANGAN / The Characteristics of Galactomannan From Various Sources And Its Utiization As An Additives in Food Products - Ihsan, Fikratul; Sugiyono, Sugiyono; Suyatma, Nugraha E. (Jurnal Penelitian dan Pengembangan Pertanian, 2022)
Galactomannans are water-soluble polysaccharides that can be extracted mainly from endosperm of legume seed. Guar gum, locust bean gum and tara gum are commercial galactomannans extracted from endosperm of legume seed that thrive in India and Pakistan. In the food industry, galactomannan is intentionally added as a thickening agent, emulsion stabilizer and gelling agent. This was due the increased use galactomannan in the food industry. The alternative sources of galactomannan began focused of researches. In Indonesia, galactomannans are extracted from the endosperm of palmae seed such as coconut, kolang-kaling and nipah. The differance of galactomannan source will affect the mannosa and galactosa (M/G) ratio of galactomannan which different result of physical characteristics including solubility, viscosity, emulsion stability, gel forming ability and stability of processing. The application of various galactomannans sources as food additives are influenced by the M/G ratio and galactomannans molecular weight. Galactomannan with weakly galactose ratio such as guar gum (M/G 2:1), tara gum (M/G 3:1) and locust bean gum (M/G 3.5:1) can be used as thickener, syneresis prevention and able to form a gel synergistically with other hydrocolloid, whereas fenugreek (M/G 1:1) which has highly galactose ratio can increase the stability of O/W (oil in water) emulsions in food products. In addition, galactomannan acts as a secondary antioxidant with Fe2+ binding mechanism. This article expose of sources, process of extraction, physical characteristics and recommeds the use of galactomannan from various sources.Keywords: Galactomannan, sources, extraction, characterization, recommendationAbstrakGalaktomanan merupakan polisakarida larut air yang diekstrak dari endosperm biji tanaman leguminase. Guar gum, locust bean gum, dan tara gum adalah galaktomanan komersial yang diekstrak dari endosperm biji tanaman leguminase yang tumbuh subur di India dan Pakistan. Pada industri makanan, galaktomanan sengaja ditambahkan sebagai bahan pengental, penstabil emulsi, dan pembentuk gel. Hal tersebut meyebabkan meningkatnya permintaan industri makanan terhadap galaktomanan komersial. Pengembagan sumber alternatif galaktomanan mulai mejadi fokus penelitian. Di Indonesia, galaktomanan diekstrak dari endosperm biji tanaman palmae seperti bungkil kelapa, kolang-kaling, dan nipah. Perbedaan sumber galaktomanan akan memengaruhi rasio manosa dan galaktosa (M/G) yang mengakibatkan terdapatnya perbedaan karakteristik fisik meliputi kelarutan, kekentalan, stabilitas emulsi, kemampuan membentuk gel, dan stabilitas terhadap kondisi pengolahan. Galaktomanan dengan rasio galaktosa yang rendah seperti guar gum (M/G 2:1), tara gum (M/G 3:1), dan locust bean gum (M/G 3,5:1) dapat digunakan sebagai pengental, mencegah terjadinya sineresis, dan memperbaiki tekstur gel hidrokoloid lain, sedangkan fenugreek gum (M/G 1:1) memiliki rasio galaktosa tinggi yang dapat meningkatkan stabilitas emulsi minyak dalam air (O/W) pada produk pangan. Selain itu, galaktomanan dilaporkan memiliki aktivitas antioksidan sekunder dengan mekanisme pengikatan logam Fe2+. Artikel ini mengungkap sumber, tahap ekstraksi, karakteristik fisik, dan merekomendasikan penggunaan galaktomanan dari berbagai sumber.Kata kunci: Galaktomanan, sumber, ekstraksi, karakteristik, rekomendasiÂ